Strategies to combat the deleterious impacts of heat stress through feed restrictions and dietary supplementation (vitamins, minerals) in broilers - Mohamed, A. S. A.; Lozovskiy, A. R.; Ali, A. M. A. (Diponegoro University, 2019)
The objective of the current study was to evaluate the impacts of feed restriction (FR) for 3 hours and/or dietary supplementation with vitamins and minerals on growth, mortality rate, some carcass traits, and serum biochemistry indices of broiler chicks under heat stress in the open housing system. A total of 240 one-week old broilers were weighed and randomly assigned into 4 equal experimental treatments. Treatment 1 (T1) was fed ad libitum on basal diets, T2 birds were fed on basal diets with FR, T3 birds were fed ad libitum on basal diets with vitamin C (200 mg) + vitamin E (200 mg) + Cr (1.5 mg ) + Zn (100 mg) per kg diet, and T4 birds were fed on basal diets with FR and combined supplementation of vitamins and minerals. It was found that growth parameters improved in T2, T3, and T4, while the mortality rate was significantly reduced compared with control. FR and feed additives (T4) revealed marked increases in serum total protein and a decrease in total serum cholesterol. It was concluded that combined effect of FR and feed additives could significantly alleviate heat stress effects for broilers by improving growth performance and decreasing mortality rate.